Temporal Variability of Atmospheric Radon‐222 Concentration at Gosan Station, Jeju Island, Korea, during 2009–2013. (23rd January 2015) - Song, Jung‐Min; Kim, Won‐Hyung; Kang, Chang‐Hee; Lee, Haeyoung; Lee, Chulkyu; Chambers, S.; Williams, A. G.
<x xml:space="preserve">Abstract</x> Atmospheric radon‐222 (radon) measurements were made from 2009 to 2013 at the Gosan station of Jeju Island, one of the cleanest regions in Korea, in order to characterize the temporal variability (on diurnal, seasonal, and annual scales) and analyze the influence of changing air mass transport pathways on observed radon concentrations. The mean hourly radon concentration over the whole period was 2441 ± 1037 mBq/m3. The seasonal cycle of radon at the Gosan station was characterized by a fall maximum and summer minimum, consistent with a reduction in nonfrozen terrestrial fetch from fall to summer. In order, the seasonal mean radon concentrations were 2962 mBq/m3 (fall) >2907 mBq/m3 (winter) >2219 mBq/m3 (spring) >1756 mBq/m3 (summer). Based on a 5‐year composite, the maximum mean monthly radon concentration in October (3100 mBq/m3) was more than twice the July minimum (1471 mBq/m3). Diurnal composite radon concentrations for the whole period increased throughout the night to a maximum of 2788 mBq/m3 at around 7 a.m., and then gradually decreased to a minimum of 2050 mBq/m3 at around 3 p.m. The winter diurnal cycle had a small amplitude due to the low variability in atmospheric mixing depth associated with recent air mass fetch over the Yellow Sea. The diurnal cycle in summer, however, exhibited a relatively large amplitude due to changes in atmospheric mixing depth associated with recent fetch over Jeju Island. Back trajectory analysis showed that high radon events were typically associated with long‐term air mass fetch over continental Asia. Specifically, the average radon concentration of air masses originating from China was about 2.4 times higher than that of air masses originating from the North Pacific Ocean.